Revitalizing Teachers' Skills in Writing Scientific Papers Through the Jigsaw Approach: Revitalisasi Keterampilan Guru dalam Menulis Karya Tulis Ilmiah Melalui Pendekatan Jigsaw - Ikhwan, Ikhwan; Abbas, Asriani; Indarwati, Indarwati; Iswary, Ery; Oddang, Faisal (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
The scientific writing training for teachers at SMP Negeri 2 Parepare was conducted in response to the low capacity of teachers to produce publishable academic works. A total of 30 teachers participated in the program, which employed an audiovisual-based Jigsaw approach characterized by collaboration and interactivity. The training methods included lectures, expert and home group discussions, writing simulations, and evaluations through pre-tests and post-tests. The results indicated an increase in teachers’ motivation and competence in developing scientific writing structures and components. The drafts produced demonstrated a solid understanding of academic structure and writing skills grounded in school-based instructional practices. This program not only enhanced teachers’ scientific literacy but also promoted sustained collaboration through the establishment of teacher working groups and supportive school policies. These findings underscore the significance of the Jigsaw-AV approach in improving teacher professionalism and overall educational quality.